Search for single-production of vector-like quarks decaying into Wb in the fully hadronic final state in pp collisions at √𝑠 = 13 TeV with the ATLAS detector - Aad, Georges; Ackermann, Anke; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; Sanfilippo, Lorenzo; et al. (Journal of high energy physics, 2025)
A search for T and Y vector-like quarks produced in proton-proton collisions at a centre-of-mass energy of 13 TeV and decaying into Wb in the fully hadronic final state is presented. The search uses 139 fb−1 of data collected by the ATLAS detector at the LHC from 2015 to 2018. The final state is characterised by a hadronically decaying W boson with large Lorentz boost and a b-tagged jet, which are used to reconstruct the invariant mass of the vector-like quark candidate. The main background is QCD multijet production, which is estimated using a data-driven method. Upon finding no significant excess in data, mass limits at 95% confidence level are obtained as a function of the global coupling parameter, κ. The observed lower limits on the masses of Y quarks with κ = 0.5 and κ = 0.7 are 2.0 TeV and 2.4 TeV, respectively. For T quarks, the observed mass limits are 1.4 TeV for κ = 0.5 and 1.9 TeV for κ = 0.7.
The ATLAS collaboration: G. Aad, A. Ackermann, L.M. Baltes, F. Bartels, S. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, T. Mkrtchyan, P. Ott, D. F. Rassloff, L. Sanfilippo, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, S. Weber, M. Wessels und weitere 2383
Gesehen am 12.11.2025